Candida infanticola and Candida spencermartinsiae yeasts: Possible emerging species in cancer patients. (February 2018) - Shokohi, Tahereh; Aslani, Narges; Ahangarkani, Fatemeh; Meyabadi, Masoumeh Fatahi; Hagen, Ferry; Meis, Jacques F.; Boekhout, Teun; Kolecka, Anna; Badali, Hamid
Abstract: Opportunistic infections due to Candida species occur frequently in intensive care settings. We investigated the prevalence of Candida species among 65 clinical specimens obtained from 200 cancer patients by phenotypic and molecular (ITS sequencing and AFLP) methods. Among the 65 yeast isolates, Candida albicans was the most commonly isolated species (n = 34, 52.3%), whereas other Candida species comprised 47.7% (n = 31) and consisted of Candida glabrata (n = 14, 21.5%), Candida tropicalis (n = 5, 7.7%) and uncommon Candida species (n = 12, 18.5%) such as Candida pelliculosa (n = 3, 4.6%), Pichia kudriavzevii (= Candida krusei, n = 2, 3.1%), Candida orthopsilosis (n = 2, 3.1%), Candida parapsilosis (n = 1, 1.5%), Candida infanticola (n = 2, 3.1%), Candida spencermartinsiae (n = 1, 1.5%), and Kluyveromyces marxianus (= Candida kefyr, n = 1, 1.5%). Candida infanticola and Candida spencermartinsiae were recovered from oral lesions of cancer patients. Matrix assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) easily confirmed these isolates as less common Candida isolates (4.6%). The in vitro antifungal susceptibilities of C. spencermartinsiae and the two strains of C. infanticola were determined according to CLSI guidelines (M27-A3). MIC results among these isolates showed they were susceptible to isavuconazole, posaconazole and voriconazole, however, fluconazole and caspofungin had high MIC values. These Candida species that may occur more commonly in infections remain unnoticed using commonly used phenotypical methods in routine microbiology laboratories. MALDI-TOF MS proved to be a more fast and robust diagnostic technique for identification of the yeasts isolated from different clinical specimens of cancer patients.